Optimal Market Structure in the Mobile Industry - François Jeanjean; Georges Vivien Houngbonon (International Telecommunications Society (ITS), 2016)
The optimal market structure in the mobile industry is an important topic in the mobile industry. In this paper, we use two theoretical frameworks and a structural estimation approach to assess the effects of market structure on consumer surplus in symmetric mobile markets. When mobile services are viewed as homogeneous products under Cournot competition, we find that consumer surplus falls with the number of operators. However, when mobile services are considered as differentiated products under Salop competition, we find an inverted-U relationship between consumer surplus and the number of mobile operators. These findings call for a case-by-case analysis of the optimal market structure in the mobile industry.
Keywords: D21; D22; L13; L40; 330; Market structure; Investment; Mobile Telecommunications